Pengaruh Edukasi Managemen Bencana Gempa Bumi terhadap Kesiapsiagaan Siswa dalam Menghadapi Gempa Bumi - Dian Lusiana Romdhonah; Adi Sucipto; Cornelia Dede Yoshima Nekada (STIKES Karya Husada Kediri, 2019)
Earthquakes are energy release events caused by movement in parts sudden earth's bowels that create seismic waves and cause natural symptoms. the cause of the large number of victims due to the earthquake is lack of public knowledge about disaster management and preparedness in the face of disasters. Based on preliminary studies conducted by researchers with interviews, it was found that there were still many students who panicked when the earthquake occurred, students also did not know how to deal with a good earthquake other than that, no one had ever given an extension. This study aims was to determine the effect of providing earthquake disaster management education on student preparedness in the face of earthquakes. Method was used quasi experiment with a pre-post test control group design. The sample size was 36 respondents divided into 2 groups. The sampling technique uses stratified random sampling. The instrument used was a questionnaire. Preparedness pretest in the control group was well prepared most of which 9 students (50%) and post-test mostly very ready for a total of 12 students (66.7%), whereas the intervention group pretest mostly prepared a total of 11 students (61.1 %) and posttest most of thewere very prepared for 13 students (72.2%). It was conclude that it is an influence of the level of preparedness pre and post test in the control group and the intervention group. There was no difference in the level ofpreparedness post test in the two group.